Silicon carbide phase transition in as-grown 3C-6H polytypes junction - Vlaskina, S.I.; Mishinova, G.N.; Vlaskin, V.I.; Svechnikov, G.S.; Rodionov, V.E.; Lee, S.W. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2013)
Perfect pure (concentration of donors ~ 10¹⁶cm⁻³ ) single crystals with joint
polytypes (hexagonal-cubic) or heterojunction investigated using low temperature (4.2 K
and 77 K) photoluminescence. Phase transformation started exactly from lamella
between polytypes. β → α ( 3C 6H ) SiC transformation distributes from lamella as
from nuclear. Photoluminescence spectra are similar to the spectrum demonstrated by
pure perfect 3C-SiC crystal in the field of mechanical deformation. In the zone of joint
polytypes and zone of the plastic deformation in perfect 3C-SiC crystal after bending, the
same stacking faults are localized. Luminescence in the disordered α-zone as a result of
phase transformation is represented by a set of intensely pronounced stacking fault
spectra. These spectra reside on more or less intense background band, which are
emission of the donor-acceptor pairs in SiC. Excitation luminescence spectra confirm
appearance of stacking faults which are responsible for metastable intermediate microand
nano-SiC structures. Solid-phase transformations β → α are related with the same
intermediate metastable microstructure that take place in the transformation α → β.